MORPHOLOGICAL STUDY OF SKELETAL MUSCLES IN A TRANSVERSE SECTION THROUGH THE LOWER ABDOMEN (ERDHEIM 10) - FUKADO, Shuichi; WATANABE, Yasuki; ISHIDA, Miyuki; MOURI, Tomoji (Journal of The Showa Medical Association, 1991)
Cross-sectional areas (CSA) of skeletal muscles observed in the CT image at the E10 level of the Erdheim's grid (the level of the lower abdomen) were measured as part of a series of studies to elucidate the development of skeletal muscle in situ. The subjects included 99 healthy adults (50 males, 49 females), grouped into five age groups (thirties, forties, fifties, sixties and seventies) . They were also grouped into three body types (A, C and D) according to their Rohrer's indices. The observed muscles were m. erector spinae, m. iliacus, m. psoas major, m. gluteus maximus, m. gluteus medius, m. gluteus minimus, m. rectus abdominis, m. abdominis internus and m. abdominis transversus. The shapes of these muscles on the CT image were traced and their CSAs were measured. The results were analyzed against the sex, age and body type, and functional differences were considered. Results: 1. The CSA of m. gluteus medius, which was largest, occupied about 33% of the whole CSA of the skeletal muscles. The CSA of gluteus maximus were second largest and occupied about 23%. The CSAs of the iliacus and psoas major occupied approximately 10%. The CSAs of the erector spinae, gluteus minimus and abdominal rectus occupied approximately 5%. The CSAs of the internal abdominis and transversus abdominis occupied about 3%. 2. In general, the CSAs of male skeletal muscle were larger than those of females. This tendency was remarkable in the case of the erector spinae, iliacus and abdominal rectus. The gluteus maximus tended to occupy a relatively larger percentage in females than in males. 3. The whole CSA of the skeletal muscles were largest in the thirties and smallest in seventies and tended to decrease with aging. The decrease with aging were remarkable in the psoas major, gluteal muscles and abdominal rectus in both sexes. The male iliacus was also remarkable for this tendency. 4. The iliacus and gluteus medius were largest in the body type C and the abdominal muscles and erector spinae were largest in body type D in both sexes. The gluteus maximus muscle was largest in body type C in males and in body type D in females.